The Effects of Worker Participation, Employee Ownership and Profit Sharing on Economics Performance: A Partial Review - Derek C. Jones; Jeffrey Pliskin (Levy Economics Institute of Bard College, 1988)
For alternative sharing arrangements we review theory on the economic effects on employment, productivity, investment, income and wealth distribution, and life cycle and survival. We find that predictions are often ambiguous and that sometimes the nature and size of the specific effect is determined in part by the particular institutional arrangements. Next recent econometric work is studied. We review studies using aggregate and industry level time series data for Japan as well as studies that use enterprise and establishment level data for firms in North America and Western Europe. Worker participation, employee share ownership and profit sharing schemes are often found to affect that studies obtained conflicting results. However, available evidence is strongly suggestive that for employee ownership schemes to have a strong positive impact they need to be accompanied by provision for worker participation in decision making.
Keywords: 330